Effects of chitosan coating and rosemary oil on rainbow trout (Oncorhynchus mykiss, W. 1792) filets - Can, Ozlem Pein; Yalcin, Halil; Arslan, Ali (Agricultural Research Communication Centre, 2018)
This study was performed to examine the effect of chitosan and rosemary oil on the shelf life changes of the rainbow trout filet. The samples divided into 4 groups. The control (I) group samples nothing were applied. The group II samples were applied solution of 2% chitosan. The group III samples were applied 2% chitosan and 0.05% rosemary oil and group IV samples only 0.05% rosemary oil. The samples of all groups storage at +4 degrees C for day 20. The microbiological (total mesophilemesophiles aerobe bacteria, H2S producing bacteria, Enterobacteria, Pseudomonas spp. and lactic acid bacteria), chemical (pH, total volatile base nitrogen and thiobarbituric acid) and sensory evaluation on days 0, 4, 8, 12, 16 and 20. Total mesophile aerobe bacteria count reached 7.2 log 10 cfu/g at samples of group I on 8 day, while 4 log 10 cfu/g samples of group III on 20 day. The result of chemical parameters, samples of group III were detected better than other groups samples during the storage time.
Keywords: Chitosan; Coating; Rosemary; Rainbow trout; Shelf life